[OP.1B.02] EFFECT OF A MULTIMODALITY TRAINING ON COGNITIVE AND VASCULAR FUNCTION IN MCI PATIENTS WITH OR WITHOUT HYPERTENSION: THE TRAIN THE BRAIN - MIND THE VESSEL STUDY. (September 2017) - Bruno, M.R.; Sicari, R.; Stea, F.; Ghiadoni, L.; Taddei, S.; Ungar, A.; Bonuccelli, U.; Tognoni, G.; Gargani, L.; D'Angelo, G.; Pratali, L.; Berardi, N.; et al.
Abstract : Objective: Environmental enrichment obtained by a multidomain training may slow cognitive decay possibly acting through an improvement in vascular function. Aim of the study is to assess the effects of a 7-month cognitive, social and physical training on cognitive and vascular function in patients with mild cognitive impairment (MCI). Design and method: In a single-center, randomized parallel-group study, 113 MCI (age 65–89 years) were randomized to multidomain training (N = 55), or usual care (N = 58). All participants underwent neuropsychological tests (including Alzheimer's Disease Assessment Scale-cognitive - ADAS-cog) and vascular evaluation, including brachial artery flow mediated dilation (FMD), carotid-femoral pulse wave velocity (PWV), and carotid intima-media thickness and distensibility. At study entry, an age-matched control group (n = 45) was also studied. Results: Compared to controls, MCI had at study entry a reduced FMD (2.97 ± 2.14 vs 3.73 ± 2.06%, p = 0.03) and hyperemic stimulus (shear rate AUC, 25.9 ± 21.2 36.7 ± 22.5 × 10–3, p = 0.008); the latter remained significantly different in covariate analysis adjusted for confounders (p = 0.04). Training improved ADAS-cog (MCI-training: 14.0 ± 4.8 to 13.1 ± 5.5; MCI-no training: 12.1 ± 3.9 to 13.2 ± 4.8; p for interaction time-treatment = 0.02) and FMD (2.82 ± 2.19 to 3.40 ± 1.81; 3.05 ± 2.08 to 2.24 ± 1.59%; p = 0.006) and prevented decline in carotid distensibility (18.4 ± 5.3 to 20.0 ± 6.6; 23.9 ± 11.0 to 19.5 ± 7.1 Pa-1; p = 0.005). The only clinical predictor of improvement of ADAS-cog in MCI-training was established hypertension (delta ADAS-cog in hypertensive patients: −2.3 ± 2.7 vs in normotensive patients 0.3 ± 5.0, p = 0.02). Furthermore, there was no correlation between changes in ADAS-cog and in vascular variables. Conclusions: A 7-month multidomain training slows, though modestly, cognitive decline, especially in hypertensive individuals. This effect is accompanied by improved systemic endothelial function and preserved carotid distensibility and it is significant only in the hypertensive subgroup.